Histological Characteristics, Fatty Acid Composition of Lipid Fractions, and Cholesterol Content of Semimembranosus and Triceps Brachii Muscles in Maremmana and Limousine Bovine Breeds - Serra, Andrea; Conte, Giuseppe; Giannessi, Elisabetta; Casarosa, Laura; Lenzi, Carla; Baglini, Alessandro; Ciucci, Francesca; Cappucci, Alice; Mele, Marcello (Frontiers in Veterinary Science, 2017)
This study examined the histological properties of Semimembranosus and Triceps brachii muscle in two different bovine breeds, Maremmana (an autochthonous breed from Tuscany, Italy) and Limousine. The animals were grazed in two adjoining pastures, received the same feed integration and were weighed monthly. The experimental period lasted from weaning (six months old) to slaughter (19 months old). Muscle samples were collected immediately after slaughter, before carcass cooling. Regarding the histological properties, the number of fibres (TNF), mean sarcolemma perimeter (MSP), cross section area (CSA), and total sarcolemma perimeter (TSP) were determined. Samples were also analysed for proximate composition, fatty acid profile of total lipids, phospholipids and neutral lipids and for total cholesterol content. Breed was a significant variation factor for the performance parameter and histological muscle fibre properties. Interestingly, despite that Maremmana being a less extensively genetically improved breed than Limousine, it showed higher weight at slaughter (+18%) and daily weight gain (+19%). Maremmana also showed smaller muscle fibres than Limousine and, consequently, the TSP was higher. This difference affected the lipid fraction distribution (Limousine was higher in phospholipids and lower in neutral lipids than Maremmana) and, consequently, the fatty acid composition of total lipids (Limousine was high in polyunsaturated fatty acids, while Maremmana was high in monounsaturated fatty acids). The results of this experiment highlight the importance of climatic and rearing conditions on the full expression of genotypic potential.